KEPEMIMPINAN DALAM ISLAM: PANDANGAN POSISI MANAJERIAL BAGI WANITA - Mismiwati, Mismiwati; Hartini, Titin (Nurani, 2013)
Abstrak: Many leaders and managers have emerged and not afew women who achieve success. These women have provedthat the feminine woman is not a weakness and inferiorcompared with masculine traits in men. Differences in thenature of women and men will make a difference also in theleadership of women and men. Characterized by maleleadership style 'command and control' was originallyconsidered to be the nicest. However, success stories of womenas leaders in an organization have proven that leadership style'command and control' is not the only way to reach the topleadership.ملخص: وقد ظھرت العدید من القادة والمدیرین ولیس عدد قلیل من النساء الذینیحققون النجاح .وقد أثبتت ھذه المرأة أن المرأة المؤنث لیس ضعف وأدنى مقارنة معالصفات الذكوریة لدى الرجال .والاختلافات في طبیعة المرأة والرجل تحدث فرقا أیضافي قیادة المرأة والرجل .یتمیز أسلوب القیادة الذكور 'القیادة والسیطرة 'كان یعتبر فيالأصل لتكون أجمل .ومع ذلك، وقصص النجاح من النساء كقادة في المؤسسة أثبتتأن نمط القیادة" القیادة والسیطرة "لیست ھي السبیل الوحید للوصول إلى القیادةالعلیا.Kata Kunci : interactive leadership, kepemimpinan wanita